2016
DOI: 10.1002/bio.3119
|View full text |Cite
|
Sign up to set email alerts
|

Systematical investigation of binding interaction between novel ruthenium(II) arene complex with curcumin analogs and ctDNA

Abstract: In this study, the interaction between a novel ruthenium(II) arene complex with curcumin analogs and calf thymus DNA (ctDNA) was investigated systematically by viscosity measurement, the DNA melting approach, multispectroscopic techniques and electrochemical methods. The absorption spectra of the ctDNA-drug complex showed a slight red shift and a weak hypochromic effect. The relative viscosity and melting temperature of ctDNA increased on addition of the drug. The evidence obtained from fluorescence competitiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0
7

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 53 publications
0
16
0
7
Order By: Relevance
“…According to EIS is also another efficient method to calculate the binding constants of foreign substances with HSA on modified electrode surface. 44 In traditional EIS curve, the semicircular portion often means the electron-transfer-limited process and the diameter of this portion represents the charge transfer resistance (R ct ) of redox probe at electrode surface. 44 Usually, the R ct value will be changed with the variation of the electrode surface property.…”
Section: Binding Constantsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to EIS is also another efficient method to calculate the binding constants of foreign substances with HSA on modified electrode surface. 44 In traditional EIS curve, the semicircular portion often means the electron-transfer-limited process and the diameter of this portion represents the charge transfer resistance (R ct ) of redox probe at electrode surface. 44 Usually, the R ct value will be changed with the variation of the electrode surface property.…”
Section: Binding Constantsmentioning
confidence: 99%
“…44 In traditional EIS curve, the semicircular portion often means the electron-transfer-limited process and the diameter of this portion represents the charge transfer resistance (R ct ) of redox probe at electrode surface. 44 Usually, the R ct value will be changed with the variation of the electrode surface property. bly, the K a-EIS value of complex 3-HSA system is about three times higher than those of other two complex-HSA systems, so complex 3 exhibits the strongest binding ability with HSA.…”
Section: Binding Constantsmentioning
confidence: 99%
“…Curcumin is a chemical component extracted from plants of Zingiberacea and used as a traditional Chinese medicine . Medical studies have demonstrated that curcumin has many pharmacological effects, such as antioxidant, anticancer, anti‐inflammatory, and antibacterial . It is used in the treatment of rheumatism, Alzheimer's disease, diabetes, and drug‐resistant tuberculosis in clinic.…”
Section: Introductionmentioning
confidence: 99%
“…[ 1–7 ] Nanoparticles bind directly to the double helix of DNA through intercalative binding, groove binding, and electrostatic binding. [ 4,8–10 ] Intercalative mode of binding refers to nanoparticles π–π stacking interactions between adjacent base pairs of DNA resulting in structural perturbation of double helix. Nanoparticles interact with the edges of base pairs either major or minor grooves through noncovalent bonds are known as groove binding.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, coulombic interactions that occur between the negatively charged phosphate groups of DNA and the cationic portion of the nanoparticles are referred to as electrostatic binding. [ 4,8–10 ]…”
Section: Introductionmentioning
confidence: 99%